PERAN ANGGOTA LEGISLATIF PEREMPUAN DI DPRD KABUPATEN BONE BOLANGO PERIODE 2019-2024 - Zulkarnain, Moh.; Mahmud, Ramli; Hamid, Saleh Al (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
This study aimed to examine the role of female legislative members in promoting gender-responsive budgeting as well as the factors that influence their participation in the functions of legislation, oversight, and budgeting The method used was qualitative with a descriptive approach, involving in-depth interviews and observations at the DPRD of Bone Bolango Regency. The results of the study show that although their number is small, female legislative members actively strive to advocate for the interests of women and vulnerable groups through various strategies, such as building alliances, conducting advocacy in official forums, and utilizing existing political opportunities. These findings highlight the importance of strengthening support and empowerment for women to solidify their roles in inclusive and gender-perspective legislative and budgeting processes. The representation of women in the DPRD of Bone Bolango Regency remains very limited and faces various structural challenges, such as male political dominance and gender stereotypes Nevertheless, female legislative members continue to play an active role in encouraging the development of gender-responsive budgeting through various strategies, including alliance-building and advocacy in official forums. This study emphasizes the importance of enhancing support and empowerment for women so that their roles in legislation, oversight, and budgeting can be more optimal, resulting in more inclusive and gender-sensitive regional policies. ABSTRAKPenelitian ini bertujuan mengkaji peran anggota legislatif perempuan dalam mendorong anggaran yang responsif gender serta faktor-faktor yang memengaruhi partisipasi mereka dalam fungsi legislasi, pengawasan, dan penganggaran. Metode yang digunakan adalah kualitatif dengan pendekatan deskriptif, melibatkan wawancara mendalam dan observasi di DPRD Kabupaten Bone Bolango. Hasil penelitian menunjukkan bahwa meskipun jumlahnya sedikit, anggota legislatif perempuan berupaya aktif memperjuangkan kepentingan perempuan dan kelompok rentan melalui berbagai strategi, seperti membangun aliansi, melakukan advokasi di forum resmi, dan memanfaatkan peluang politik yang ada. Temuan ini menegaskan pentingnya peningkatan dukungan dan pemberdayaan perempuan untuk memperkuat peran mereka dalam proses legislasi dan penganggaran daerah yang inklusif dan berperspektif gender. Keterwakilan perempuan di DPRD Kabupaten Bone Bolango masih sangat terbatas dan menghadapi berbagai tantangan struktural, seperti dominasi politik laki-laki dan stereotip gender. Meski demikian, anggota legislatif perempuan tetap aktif berperan dalam mendorong penyusunan anggaran yang responsif gender dengan berbagai strategi, termasuk membangun aliansi dan melakukan advokasi di forum resmi. Penelitian ini menegaskan pentingnya peningkatan dukungan dan pemberdayaan perempuan agar peran mereka dalam legislasi, inklusif dan berperspektif gender.